Digital simulations for improving education [ learning through artificial teaching environments - Baek, Youngkyun; Gibson, David (Information Science Reference, 2009)
"This book is for anyone who is looking into games and simulations with an eye to their potential for improving teaching and learning"--Provided by publisher.